The Impact of Sharia Compliance on Islamic Bank Customer Loyalty: A Systematic Literature Review - Marlius, Doni; Dwita, Vidyarini; Abror, Abror; Wardi, Yunia (Jurnal Sains Sosio Humaniora, 2026)
This study aims to analyze the development of literature on sharia compliance in relation to Islamic bank customer loyalty, identify the influence of sharia compliance on customer loyalty, evaluate differences in research findings across various geographical and cultural contexts, examine the interaction of sharia compliance with contemporary factors such as digital transformation, and identify research gaps and future research agendas. The study employs a Systematic Literature Review (SLR) approach guided by PRISMA. Bibliometric analysis was conducted using VOSviewer software to map the development of research themes, conceptual relationships, and trends related to sharia compliance and Islamic bank customer loyalty. The synthesis results indicate that sharia compliance literature has evolved from a normative approach to a strategic perspective, positioning sharia compliance as a source of competitive advantage and a driver of long-term customer relationships. Sharia compliance has been shown to positively influence Islamic bank customer loyalty, although its effect is not always direct and is often mediated by factors such as trust, satisfaction, service quality, and customer experience. Furthermore, differences in findings were observed across geographical and cultural contexts, with countries of high religiosity tending to regard sharia compliance as a primary determinant of loyalty. This study also identifies research gaps, including the dominance of adoption-focused studies over long-term loyalty, limited exploration of sharia governance, and the scarcity of research in the Indonesian context and the digital era.